2014
DOI: 10.1364/oe.22.011079
|View full text |Cite
|
Sign up to set email alerts
|

Vortex algebra by multiply cascaded four-wave mixing of femtosecond optical beams

Abstract: Experiments performed with different vortex pump beams show for the first time the algebra of the vortex topological charge cascade, that evolves in the process of nonlinear wave mixing of optical vortex beams in Kerr media due to competition of four-wave mixing with self-and cross-phase modulation. This leads to the coherent generation of complex singular beams within a spectral bandwidth larger than 200nm. Our experimental results are in good agreement with frequency-domain numerical calculations that descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…Extensive numerical simulations confirm the physical mechanisms of the processes involved. New results here in addition to these in [26] are: i) The single-beam pumping experiment serving as a proof for the main findings obtained with the two-beam pumping scheme;…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Extensive numerical simulations confirm the physical mechanisms of the processes involved. New results here in addition to these in [26] are: i) The single-beam pumping experiment serving as a proof for the main findings obtained with the two-beam pumping scheme;…”
Section: Introductionsupporting
confidence: 58%
“…The main results [26] are worth mentioning: If the two pump beams (e.g. at frequencies ω 5 and ω 6 ) carry OVs with opposite unit charges, the generated signals at frequencies ω 4 and ω 7 carry charge-three vortices of different signs which, eventually, decay into three charge-one vortices with highly overlapping cores.…”
Section: B Single-beam Pumping With Doubly-charged Ovmentioning
confidence: 99%
See 1 more Smart Citation
“…In these experiments, topological charge measurements verified a predicted orbital angular momentum algebra (OAM-algebra). This OAM-algebra was later verified in experiments given in [16,17]. In [16] the authors employed two optical parametric amplifiers to produce two spectrally separated beams that were crossed in a Raman active crystal, and in [17] the authors utilized a dichroic beam splitter and spectral filters.…”
Section: Introductionmentioning
confidence: 78%
“…Recently a number of investigations involving the nonlinear interaction of optical vortices with matter appeared in the literature [15][16][17]. In experiments presented in [15], the authors crossed time-delayed chirped pulses in a lead tungsten PbWO 4 crystal and demonstrated for the first time the coherent transfer of optical angular momentum in the generation of cascaded Raman sidebands.…”
Section: Introductionmentioning
confidence: 99%